A study to evaluate and compare the results of different modalities of operative treatment of distal femoral fracture - Dr. Manav Moda; Dr. Sachin Samaiya (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Aim: of the study was to evaluate and compare the results of different modalities of operative management of distal femoral fractures. Material and Method: The present study was conducted on 48 patients having fractures of the distal femur (involving distal 15cm of the femur).The cases were picked up from the patients treated at two tertiary care hospitals by open reduction and internal fixation from July 2014 to July 2018. Both anatomical and functional results were analyzed and graded. Results: Age of the patients operated upon ranged from 16-75 years (Mean age 41.6years). Male-dominated in our series, comprising 72.91% (35 out of 48 cases). All patients in our series had unilateral involvement of distal femoral fractures. The right side was however involved more i.e. 29 out of 48 (60.4%). The most common mode of the accident in our series was automobile accident (91.67%).42 out of 48 were closed fractures (87.5%), whereas the remaining 6 patients (12.5%) had open grade I type of fracture. Associated injuries were observed in 13 out of 48 cases in our series (27%). In most of the patients, the implant used was either a dynamic condylar screw or a distal femur plate. 41 out of 48 patients (85.42%) were discharged from the hospital within 7 days. Conclusion: For Distal femoral fractures early open reduction, rigid fixation allows accurate anatomical alignment, reconstruction of articular surfaces joint congruity and it offers opportunities for early post-operative knee mobilization and prevents frequent problems of limitation of knee movements, nonunion and osteoarthritis.